Differential responses of Bactrocera dorsalis and its parasitoids to headspaces of different varieties of tree-attached mango fruits and the associated chemical profiles - Miano, Raphael Njurai; Mohamed, Samira A.; Cheseto, Xavier; Ndlela, Shepard; Biasazin, Tibebe Dejene; Yusuf, Abdullahi Ahmed; Rohwer, Egmont; Dekker, Teun (Frontiers in Ecology and Evolution, 2022)
Bactrocera dorsalis (Hendel) is a major pest of fruit and vegetable worldwide with documented losses of up to 100%. Various management techniques including use of parasitoids, such as Fopius arisanus (Sonan) and Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) within the context of the Integrated Pest Management (IPM) approach have been deployed for its control. The effectiveness of parasitoids is well understood, but knowledge of the semiochemicals that mediate their behaviour, as well as that of the host fruit fly to tree-attached mangoes, is lacking. Here, we first compared the attractiveness of the above-mentioned fruit fly and its parasitoids to volatiles of different treatments (non-infested physiologically mature unripe and ripe mangoes, mangoes newly exposed to ovipositing B. dorsalis, and mangoes on day 7 and day 9 post-oviposition) of tree-attached Kent, Apple, and Haden mangoes relative to control (clean air). The fruit fly was significantly more attracted to the mango volatiles (up to 93%) compared to control (clean air). Fopius arisanus was significantly more attracted to mangoes with ovipositing fruit flies (68-76%) while D. longicaudata was significantly more attracted to day 9 post-oviposited mangoes (64-72%) compared to the control. Secondly, we elucidated the headspace volatile profiles of the non-infested and infested tree-attached mangoes using gas chromatography linked to mass spectrometry (GC-MS). The volatiles revealed various types of organic compounds with qualitative and quantitative differences where majority were esters-33.8%, followed by sesquiterpenes-16.4%, and monoterpenes-15.4% among others. Most compounds had higher release rates in headspace volatiles of fruit fly-infested mangoes. Lastly, we harvested the infested mangoes and incubated them for puparia recovery. The number of puparia recovered varied according to the mango variety with Apple mango registering 81.7% of the total, while none was recovered from Kent. These results represent the first report of the changes in the headspace components of non-infested and infested tree-attached mangoes and the associated differential responses of the mentioned insects. A follow-up study can reveal whether there is a convergence in olfactomes which is significant when developing baits that selectively attract the fruit fly and not its natural enemies, and fill the knowledge gap from an evolutionary ecological perspective.